Structure of Mangrove Vegetation Patterns Based on Salinity Differences in Jangkang River, Bengkalis Island, Riau - Ria Saputra, Eki; Setyawatiningsih, Sri Catur; Mahatma, Radith (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangroves in Sungai Jangkang, Bengkalis Island, are affected by anthropogenic activities and environmental factors, with salinity being the most influential environmental factor. This study aims to describe the structure of mangrove vegetation patterns based on variations in salinity. The research was conducted in the Jangkang River, Bengkalis Island, in March 2024. Representative areas of three salinity zones along upstream, midstream, and downstream were selected. The species present were assessed for density, frequency, dominance, and importance index. The salinity in the upstream section was 5 ‰, in the midstream 8 ‰, and in the downstream 18 ‰. Four species from four families were found in the upstream section, three species from three families in the midstream, and eight species from seven families in the downstream section. Rhizophora apiculata was the most dominant species and had the highest importance index (INP) in the Jangkang River. Mangrove species diversity in the upstream and midstream sections of the Jangkang River was classified as low (H' < 1), while the downstream section had moderate diversity (1 < H' < 3).